INTEGRATING MULTICULTURAL EDUCATION IN EFL CLASSROOMS: TEACHERS' PERSPECTIVES, CHALLENGES AND OPPORTUNITIES - Fheby Indriyanti Nurpratiwi; Reni Apriani; Junita Siahaan (Universitas PGRI Sumatera Barat, 2025)
Multicultural education plays a significant role in fostering students' language learning by enhancing cultural awareness, motivation, and communicative competence. This study explores the perspectives of EFL teachers on how integrating multicultural education impacts language learning in Multiculturalism and Language Education course at La Tansa Mashiro University. Using a qualitative case study approach, data were collected through classroom observations, documents analysis and interviews involving two EFL teachers actively involved in EFL teaching and twenty students in this course, to explore the complexities and nuances of integrating multicultural education. The findings reveal that teachers’ awareness, understanding and strategy in integrating multicultural education in language teaching improves students' engagement, promotion of critical thinking and linguistic proficiency of appreciating and thriving in a diverse world. However, challenges such as the need for teacher training, culturally responsive teaching materials to balance with standardized curriculum requirements, students’ limited intercultural exposure that may lead to potential resistance or discomfort during discussions of culturally sensitive topics, and institutional support in enhancing multicultural education in EFL classrooms. In conclusion, this study provided valuable insights for teachers, institutions, and policymakers to improve multicultural education activities to maximize learning outcomes in EFL setting.Keywords: multicultural education, EFL Teachers, language learning, intercultural competence, case study